Carbon Budget of an Eastern North Carolina Pocosin Following Nutrient Gradient Manipulation - Law, Sydni L (East Carolina University, 2018)
Wetlands store ~25-30% of the earth's soil pool of carbon. Seventeen percent of the US' wetlands are found in North Carolina (NC) where 70% of NC's freshwater wetlands are pocosin peatlands. Pocosins are known for thick peat layers that store substantial amounts of carbon and other nutrients, particularly nitrogen. Since the 1920s, 50% of NC's pocosins have been degraded for agricultural purposes and almost all of NC's pocosins have been altered at least once in some way. This research was carried out in a pocosin located on East Carolina University's West Research Campus (ECU-WRC) that drains into the Neuse and Tar Rivers, contributing to downstream river and estuary health by retaining large amounts of nutrients. The aim of this research was to determine how these freshwater ombrotrophic bogs budget and store carbon when the availability of phosphorus, the limiting nutrient, increases across a P-fertility gradient. CO2 flux calculations were made using static greenhouse gas chambers and used as indicators of net ecosystem metabolism. Above- and belowground biomass were also collected to determine biomass C allocation. Soil samples were taken prior to the beginning of the experiment and then at 6 and 12 months afterwards to examine changes in soil nutrient concentrations. Changes in above- and belowground biomass allocation, C allocation in roots and shoots, CO2 flux between treatments, and soil nutrient stoichiometric ratios were compared to determine how increasing P availability in the soil affected the wetland's C budget and soil chemistry. Results show that increasing the limiting nutrient in pocosins initially decreases CO2 flux, but only at low amounts of P applied. Additionally, results from biomass and soil analyses indicate that while P-fertility manipulations had local effects, there was a strong seasonal effect that the experiment did not cancel out. Demonstrating changes in carbon budgeting within a pocosin following nutrient application can provide insight into the fate of degraded peatlands and their potential influence on downstream freshwater resources, such as the ones that occur along the southeastern Coastal Plain of the U.S.
Keywords: carbon budget; pocosin; phosphorus; N:P ratios; Wetland ecology--North Carolina; Peatland ecology--North Carolina; Carbon dioxide mitigation--North Carolina; Nutrient pollution of water--North Carolina